Updated Evaluation of the Diagnostic Performance of Double Contrast-Enhanced Ultrasonography in the Preoperative T Staging of Gastric Cancer: A Meta-Analysis and Systematic Review - Zhang, Xin; Yao, Jun; Zhang, Yu; Huang, Xin; Wang, Weijun; Huang, Hejing (Frontiers in Oncology, 2022)
Objective: To systematically evaluate the diagnostic performance of double contrast-enhanced ultrasonography (DCEUS) in the preoperative T staging of gastric cancer (GC). Methods: Literature searches for eligible studies were performed using MEDLINE, EMBASE, and Cochrane Library. The pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds ratio, and the area under the summary receiver operating characteristic (SROC) curve of DCEUS in the diagnosis of each T stage tumor were calculated. Meta-analyses were performed to obtain the pooled effects of risk ratio (RR) with 95% confidence interval (CI) in the comparison of DCEUS with CT/EUS. Results: A total of 8 studies including 1232 patients were identified for inclusion in this meta-analysis. The pooled sensitivity and specificity were 0.78 (95% CI=0.64-0.88) and 0.98 (95% CI=0.96-0.99) for T1, 0.81 (95% CI=0.76-0.86) and 0.96 (95% CI=0.91-0.98) for T2, 0.88 (95% CI=0.84-0.91) and 0.85 (95% CI=0.79-0.90) for T3, and 0.81 (95% CI=0.69-0.89) and 0.96 (95% CI=0.93-0.97) for T4. Moreover, DCEUS demonstrated significant superiority to CT in diagnosing T1 (RR=1.57, 95% CI=1.20-2.05, p=0.001) and T2 (RR=1.41, 95% CI=1.16-1.71, p=0.001), and to EUS in diagnosing T3 (RR=1.24, 95% CI=1.08-1.42, p=0.003) and T4 (RR=1.40, 95% CI=1.09-1.79, p=0.008). However, it showed lower diagnostic accuracy than EUS in T1 tumors (RR=0.77, 95% CI=0.62-0.94, p=0.013). Conclusions: DCEUS is a feasible complementary diagnostic tool for clinical T staging of GC. However, it is still far from a definitive conclusion that the use of DCEUS is proposed in routine clinical practice.